Identification of terpenoids volatilized from Thymus vulgaris L. by heat treatment and their in vitro antimicrobial activity. (April 2016) - Eguchi, Yumi; Widiastuti, Ani; Odani, Hiromitsu; Chinta, Yufita Dwi; Shinohara, Maki; Misu, Hideyuki; Kamoda, Haruna; Watanabe, Tomofumi; Hasegawa, Morifumi; Sato, Tatsuo
Abstract: Enhanced antifungal activity by hot water treatment at 50 °C 20 s against Botrytis cinerea Pers. ex Fr., a gray mold pathogen was evaluated in thyme ( Thymus vulgaris L.) Thymol, p -cymene, and γ-terpinene were detected as the main volatile compounds in thyme plants. Emission of p -cymene and γ-terpinene from thyme increased after treatment, whereas amount of thymol released did not change, suggested that existence of a thermo-dependent synthesis pathway of p -cymene and γ-terpinene. Volatile p -cymene inhibited mycelial growth of pathogen at 0.50 μL/ml, whereas γ-terpinene had an inhibitory effect at 0.05, 0.10, and 0.50 μL/ml. Transcript level of γ-terpinene gene increased after 24 h of treatment. As a conclusion, heat treatment enhanced antifungal activity by volatile terpenoids synthesized by thermo-dependent synthesis pathway of them in thyme. Highlights: Volatile organic components of Thymus vulgaris have antimicrobial activity. Thyme volatile components inhibited Botrytis cinerea mycelial growth after heat treatment. Thymol, p -cymene, and γ-terpinene were the main volatile compounds. The biosynthetic gene expression of γ-terpinene tended to increase after heat treatment. Heat treatment of Thymus vulgaris may be useful for plant disease control.